2018
DOI: 10.1017/s0144686x18000041
|View full text |Cite
|
Sign up to set email alerts
|

Living arrangement preferences and realities for elderly Chinese: implications for subjective wellbeing

Abstract: This article investigates the determinants of preference for intergenerational co-residence and examines the effects of living arrangement concordance (i.e.having a match between preference and reality) on the subjective wellbeing (SWB) of older Chinese. Data were derived from the China Health and Retirement Longitudinal Study (CHARLS) national baseline conducted in 2011. This allows for two different measures of the affective approach to SWB: depression and happiness. This article found living arrangement pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
4
25
0
Order By: Relevance
“…The intergenerational co-residence and taking care of parents remain an important obligation of children. These actions are also signs of respect and social support for the older generation, which may directly protect the mental health and wellbeing of older Chinese parents [82][83][84][85]. Therefore, our participants may rate lower scores on certain items of BIT (e.g., I feel a sense of belonging in my community; There are people who appreciate me as a person), which reduce the internal consistency of BIT.…”
Section: Limitationsmentioning
confidence: 96%
“…The intergenerational co-residence and taking care of parents remain an important obligation of children. These actions are also signs of respect and social support for the older generation, which may directly protect the mental health and wellbeing of older Chinese parents [82][83][84][85]. Therefore, our participants may rate lower scores on certain items of BIT (e.g., I feel a sense of belonging in my community; There are people who appreciate me as a person), which reduce the internal consistency of BIT.…”
Section: Limitationsmentioning
confidence: 96%
“…The rapid socioeconomic transition in China has changed older people's family arrangements voluntarily or involuntarily. For instance, some older adults may prefer not to live in a multigenerational setting as they increasingly value their own privacy and prefer to avoid intergenerational conflicts; 13 whereas others may be forced into living in an 'empty nest' as their children migrate for marriage and work. 14 In addition, the abovementioned meta-analysis 5 and the Lancet Commission report 4 heavily relied on studies conducted in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Our results, however, indicate that living in two-generation households might not be associated with higher SWB for older adults compared to those living with a spouse only. Empirical studies have found that living in a preferred arrangement is more important for older adults' SWB than following societal norms (Chen, 2019). A growing percentage of contemporary Chinese older adults may prefer to live with their spouses only.…”
Section: Discussionmentioning
confidence: 99%